VIRTUE IN ISLAMIC ECONOMICS: ANALYSIS OF THE ETHICO-RELIGIOUS MEANING OF THE WORD IQTISAD IN ISLAM - Mohammad Muzwir R. Luntajo; Nur Shadiq Sandimula; Fitria Ayu Lestari Niu; Chadijah Haris; Faradila Hasan (Academic Bright Collaboration, 2026)
The term Iqtishad carries an original ethico-religious meaning that has been displaced by modern Western economic connotations, rendering its inherent principle of moderation dormant in contemporary Islamic economic discourse. This study seeks to recover that original meaning and establish Iqtishad as a foundational ethical virtue in Islamic economics. This study employs qualitative library research using classical Arabic lexicons, Qur'anic exegesis, Prophetic hadith, and classical Islamic scholarly heritage (turath), analyzed through the semantic analysis method of Syed Muhammad Naquib al-Attas, tracing the root qashd across six Qur'anic verses, ten hadith traditions, and works of Miskawayh, al-Ghazali, and al-Thusi. Iqtishad is identified as a virtue (fadhilah) derived from 'iffah (self-restraint), representing the middle position between israf (extravagance) and taqtir (miserliness), with five sub-virtues: sakha' (generosity), qana'ah (contentment), intizham (self-regulation), waqar (tranquility), and wara' (piety). Findings are interpretive and text-based, requiring further empirical research to test applicability in actual economic behavior and policy contexts. This study uniquely applies al-Attas' semantic method to Islamic economics, systematically categorizing Iqtishad within classical virtue ethics and offering an epistemically indigenous foundation for the discipline.